2016
DOI: 10.1002/ams2.197
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the delayed onset of neuropsychologic sequelae following carbon monoxide poisoning

Abstract: AimCarbon monoxide (CO) poisoning often manifests delayed neuropsychological sequelae. The risks and preventive factors for the development of delayed neuropsychological sequelae are controversial at present. The purpose of this retrospective study was to assess the risk factors for this condition.MethodWe studied 81 patients with CO poisoning admitted to the Critical Care and Emergency Medicine Center at the Kansai Medical University from 2006 to 2012. All patients (64 males and 17 females; average age, 45.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 16 publications
3
10
0
1
Order By: Relevance
“…57 Follow-up of our patients for 6 months after discharge showed that DNS manifestations were reported by six patients (12%), which is nearly similar to the rates (14-16.5%) reported by previous studies. 46,47,58,59 However, both higher rates (24.1-26%) 21,60 and lower rates of DNS (9.8%) 23 were also found in other studies. These discrepancies in the incidence of DNS among the studies may be due to various factors such as the age of the studied patients, the duration of exposure to CO, the delay before receiving medical care, and the concentration of the gas.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…57 Follow-up of our patients for 6 months after discharge showed that DNS manifestations were reported by six patients (12%), which is nearly similar to the rates (14-16.5%) reported by previous studies. 46,47,58,59 However, both higher rates (24.1-26%) 21,60 and lower rates of DNS (9.8%) 23 were also found in other studies. These discrepancies in the incidence of DNS among the studies may be due to various factors such as the age of the studied patients, the duration of exposure to CO, the delay before receiving medical care, and the concentration of the gas.…”
Section: Discussionsupporting
confidence: 61%
“…52,53 In agreement with our results, Park et al 47 found a nonsignificant increase in COHb and a significant increase in serum S-100b protein levels in patients who developed DNS. Moreover, Pepe et al, 21 Moon and Kim, 60 Kudo et al, 58 and Kitamoto et al 59 found a lack of correlation between COHb level and DNS. Also, Di et al 67 and Hassan et al 46 reported that serum S-100b levels were significantly higher in patients with DNS.…”
Section: Roc Curve Variablesmentioning
confidence: 98%
“…8 Possible risk factors identified for DNS include advanced age, rhabdomyolysis and elevated creatine kinase, CO exposure due to charcoal burning, prolonged CO exposure, low Glasgow Coma Scale score, bed sores, ECG changes and changes on neuroimaging (especially in the basal ganglia and specifically the globus pallidus). 4,7,9…”
Section: Discussionmentioning
confidence: 99%
“…Nicht zuletzt bleibt noch zu erwähnen, dass die Bildgebung bei Patienten mit akuter oder verspäteter Enzephalopathie auch unauffällig ausfallen kann [21]. Auch bei dem von uns beschriebenen Patienten waren die Veränderungen der Gp eher von diskreter Ausprägung und hätten, bei fehlendem Wissen über die Grunderkrankung leicht übersehen werden können.…”
Section: Diagnostikunclassified